The Dental Arch Length and Width Differences Between Males and Females Ages 7-9 Years-Old Children - Rahmawati, Atiek Driana; Surgawi, Ambawani Widad (Jurnal Kesehatan Gigi, 2025)
The dental arch consists of teeth that develop on the jawbone. The shape and size of the dental arch are important components in orthodontic diagnosis and treatment planning. This study is to determine if there is a relationship between gender and the length and width of the dental arch in children aged 7 to 9 years. This research is an observational study using a cross-sectional design. The sample included 72 subjects for the study, consisting of girls and boys ages 7, 8, and 9, who met the inclusion and exclusion criteria. The dental arch width was measured at the inter-canines and inter-molars by digital sliding calipers. Anterior and posterior size of dental arch length measured from the midpoint between the right and left permanent central incisors perpendicular to the inter-canines and inter-molars. The Independent Sample t-Test results showed no significant differences in any parameters at the age of 7 years. However, at 8 years, a significant difference was observed in the intermolars of the mandible, while at 9 years, a significant difference was found in the intercanines width of the mandible between males and females. These findings indicate developmental variations in mandibular growth based on gender.